Crystal structure of a human GABAA receptor - Miller, P; Aricescu, A (Nature Publishing Group, 2014)
Type-A γ-aminobutyric acid receptors (GABAA Rs) are the principal mediators of rapid inhibitory synaptic transmission in the human brain. A decline in GABAA R signalling triggers hyperactive neurological disorders such as insomnia, anxiety and epilepsy. Here we present the first three-dimensional structure of a GABAA R, the human β homopentamer, at 3Å resolution. This structure reveals architectural elements unique to eukaryotic Cys-loop receptors, explains the mechanistic consequences of multiple human disease mutations and shows an unexpected structural role for a conserved N-linked glycan. The receptor was crystallized bound to a previously unknown agonist, benzamidine, opening a new avenue for the rational design of GABA A R modulators. The channel region forms a closed gate at the base of the pore, representative of a desensitized state. These results offer new insights into the signalling mechanisms of pentameric ligand-gated ion channels and enhance current understanding of GABAergic neurotransmission. © 2014 Macmillan Publishers Limited. All rights reserved.